DIAGNOSTICS OF MEMORY CHIPS IN MICROPOCESSOR- BASED UNITS - Nevludov, I. Sh.; Shostak, B. A.; Babay, O. N.; Yurieva, S. V. (Radio Electronics, Computer Science, Control, 2010)
A new method of memory chips diagnostics is described which makes it possible to perform diagnostics of operating memory devices. The block diagram of hardware component is shown and software structure is described, which permits to implement the developed method of memory chips diagnostics.